The Significant of Fashion Ethics Education on Young Fashion Designers and Entrepreneurs - Yoanita Kartika Sari Tahalele (Humaniora, 2020)
The research aimed to examine the relationship and understand the significance of ethical fashion education to young fashion designers and entrepreneurs’ value systems and ethical behavior. The research applied a descriptive qualitative method based on focus group discussion using purposive sampling. Data were collected from six young fashion designers and entrepreneurs, who graduated from Fashion Design and Business at Universitas Ciputra Surabaya and had ever attended Fashion Ethics class on their seventh semester. The research result shows that Fashion Ethics education is important and gives a positive impact on participants’ ethical values and behavior. Furthermore, some existing personal traits that came from family, as well as previous formal education, significantly influence people’s value system and ethical behavior, which cause different impacts and results of the program among participants. Meanwhile, the religious background does not have a significant influence on the result. In conclusion, the Fashion Ethics program has a positive effect on young fashion designers and entrepreneurs’ ethical values and behavior.